Early intervention with extracellular vesicles derived from human umbilical cord mesenchymal stem cells enhances survival and functional recovery after spinal cord injury in rats - Cipriano, Barbara Porto; Cunha, Rachel Santana; Santana, Thaís Alves de; Silva, Kátia Nunes da; Loiola, Erick Correia; Figueiredo, Júlio César Queiroz; Silva, Elisama Araújo da; Lima, Adne Vitória Rocha de; Rossi, Erik Aranha; Silva, Igor Campos da; Nascimento, Ravena Pereira do; Costa, Silvia Lima; et al. (Frontiers in Pharmacology, 2025)
IntroductionSpinal cord injury (SCI) is a devastating condition with high mortality and limited treatment options. Mesenchymal stem cell (MSC)-derived extracellular vesicles (EVs) have emerged as promising cell-free therapies due to their immunomodulatory and neuroprotective properties. Here, we evaluated the therapeutic potential of EVs derived from human umbilical cord MSCs in a rat model of SCI.MethodsAdult male Wistar rats were randomized into three groups: control, SCI, and SCI treated with a single intralesional dose of EVs. Locomotor recovery was assessed by the Basso, Beattie & Bresnahan (BBB) score, while survival, neuroinflammation, histological alterations, and biodistribution were systematically analyzed.ResultsEV administration improved 30-day survival, and locomotor performance from day 7, and was associated with sustained reductions in pro-inflammatory cytokines (IL-1β, TNF-α) alongside increased levels of anti-inflammatory cytokines (IL-10) and neurotrophic factors (BDNF). Histological and immunofluorescence analyses showed attenuated microglial activation and astrocytic reactivity, accompanied by reduced lesion size and glial scar formation. In vivo imaging demonstrated accumulation of labeled EVs at the injury site, with peak retention at day 7 post-injection.DiscussionTogether, these findings demonstrate that early intralesional delivery of MSC-EVs enhances survival, modulates the inflammatory response, and promotes functional recovery after SCI, supporting further translational development of EV-based interventions for SCI.